Sulwe - Nyong'o, Lupita (New York : Simon & Schuster Books for Young Readers, 2019)
When five-year-old Sulwe's classmates make fun of her dark skin, she tries lightening herself to no avail, but her encounter with a shooting star helps her understand there is beauty in every shade.
School Library Journal, October 2019
Pub Weekly, August 2019
Kirkus Starred, August 2019
2.2.
K-3.
O
Keywords: Self-acceptance -- Juvenile fiction; Kenya -- Juvenile fiction; Stars -- Juvenile fiction; Self-acceptance -- Fiction; Kenya -- Fiction; Stars -- Fiction; African Americans -- Juvenile fiction; Black people -- Kenya -- Fiction